Organização do trabalho e aspectos de saúde associados à capacidade de trabalho em pilotos da aviação comercial. - Pellegrino, Pollyanna (2016)
Work in man's life is of priority when can get personal achievements, professional and also consequences that the work process triggers in the economic sector and in the public health. However, for that happen it is important that the employee is apt and able to work. The airline pilot, who practices a complex professional activity, requires different skills and a great cognitive and physical ability. Although, the current working conditions of the pilots, which include irregular work schedules, intense rhythm and long working hours, psychological pressure, in addition to stress, may contribute to the early functional aging. Objective: Analyze the association between the work organization and health aspects with the work ability in the commercial aviation pilots. Methods: Epidemiological and cross-sectional study sample of 1234 pilots of commercial aviation that carried out flights of domestic and international routes and who were registered at the Brazilian Association of Civil Aviation Pilots (ABRAPAC). Data collection was conducted through online questionnaire with sociodemographic data, health & lifestyle and work. Variables were described by absolute and relative frequencies. To compare between the proportions were used the Pearson¿s Chi-square hypothesis tests or Fisher¿s exact tests. To compare the means Work Ability Index (WAI) for according to occupational stress were used ANOVA test and post hoc Bonferroni. To evaluate the factors associated with inability to work was performed Poisson regression, with robust variance. The significance level for all tests was 5%. Statistical analyzes were performed in STATA 12.0. Results: Most of the pilots were male (97.1%) lived with a partner (84.6%), had complete or incomplete graduation (71.3%) and aged below 39 years old (52.4%). The prevalence of moderate or low WAI was 21%. It was found that not getting enough sleep (PR 1.59, 95% CI 1.27-2.00), have less than ten days off per month (PR 1.67, 95% CI 1.29-2.17), frequent operational delays (PR 1.43, 95% CI 1.00-1.56) and have monthly day flight 66 hours or more (PR 1,24, IC 95% 1.00-1.56) were risk factors for moderate or low WAI, being the passive job (PR 0.58, CI 95% 0.39-0.85) was a protective factor. Conclusion: The work organization was a determining factor for the decrease in capacity for work of the commercial pilots studied, in particular the aspect related to shift work and night and their impact on quality of sleeping.